Synthesis and x-ray crystallographic analysis of 4, 6-di-O-acetyl-2, 3-dideoxy-α-d-threo-hexopyranosyl cyanide. (29th April 2016) - Rotella, Madeline; Giovine, Matthew; Dougherty, William; Boyko, Walter; Kassel, Scott; Giuliano, Robert
Highlights: Stereoselective synthesis of a novel glycosyl cyanide. Complete structural assignments based on 2D NMR techniques and x-ray crystallographic analysis. Graphical abstract: Abstract: The glycopyranosyl cyanide 4, 6-di-O-acetyl-2, 3-dideoxy-α-d -threo-hexopyranosyl cyanide has been synthesized from tri-O-acetyl-d -galactal by reaction with trimethylsilyl cyanide in the presence of boron trifluoride diethyl etherate followed by catalytic hydrogenation. The synthesis provides the α-anomer stereoselectively, the structure of which was assigned based on 2D NMR techniques and x-ray crystallography.